用微针阵列递送肉毒杆菌 (2021)
用于治疗受试者的疾病、病症、或状况的治疗毒素剂型可包括微针阵列和装载到微针阵列用于向受试者施用的治疗有效量的治疗毒素。另外，治疗受试者的疾病、病症、或状况的方法可包括将治疗有效量的治疗毒素通过微针阵列向受试者施用。 A therapeutic toxin dosage form for treating a disease, disorder, or condition in a subject can include a microneedle array and a therapeutically effective amount of a therapeutic toxin loaded to the microneedle array for administration to the subject. Additionally, a method of treating a disease, disorder, or condition in a subject can include administering a therapeutically effective amount of a therapeutic toxin to the subject via a microneedle array.